PERCOBAAN PEMIJAHAN IKAN PUYU (Anabas testudienus) - Ahmad, Muchtar; Fauzi, M (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
In order to fulfill a prerequisite domesticated and culture of climbing perch, anexperiment have been executed to spawn the fish in the circular concrete tank ofdiameter 1,2 m x 0,5 m in depth with 6 – 8 cm water depth and in the wooden tankcovered with blue color plastic of 1 m x 2.5 m x 0.5 m with water depth of 23 – 25cm. Into the respective tanks spawned mature climbing perch of 7 – 18 cm in lengthwith sex ratio of one female and two male broodstocks and two pairs of male andfemale broodstock with several water hyacinth. The broodstocks were feed on ricebrean and old water hyacinth as detritus. Water temperature was around 22 – 32 oC.Within three weeks the fish spawned and hundred of fish larvae of 1 – 1,5 cm inlength of two weeks old were found with survival rate less than one percent.Meanwhile within the next two weeks the fish grow to 2 – 2,5 cm with body colordarkened. Hence, the successful of climbing perch spawn in the control environmentwithout any modification of its condition support that the fish is well domesticatedand further hatchery development for the fish as well as its culture in the pond andfloating cage are feasible. However further study on proper sex-ratio, hatchery designand engineering, as well nurturing of larvae are a new interesting challenge.